Technical Trend of Friction Reduction in Engine Bearings - Shu Kamiya (Japanese Society of Tribologists, 2017)
Currently, the demand for improved fuel consumption rates in automobiles has increased because of growing concerns related to global warming and energy conservation. Because of these concerns, the number of automobiles equipped with hybrid systems, also known as hybrid electric vehicles (HEVs), is increasing. In hybrid electric vehicles, a reduction in engine bearing friction is required to improve fuel economy, particularly under the operating conditions with low oil temperature. In this study, two cutting-edge technical methods used for reducing engine-bearing friction are described. One method utilizes a resin coating as a low-friction material, which is including graphite in the coating instead of MoS2 and CaCO3. The other utilizes a Partial Twin Groove (PTG) bearing as a surface design. PTG bearing has an effect of quick warm-up oils on the bearing surface by reducing oil leakage. Narrow grooves located on the bearing surface enhance the suction of oil from the outside of the bearing to the inner surface. As a result, engine oil recirculates in the bearing and the oil temperature is quickly raised, particularly under cold conditions. This design offers a fuel efficiency of approximately 0.14%.